A new copper ionophore N1, N3-Bis [[3,5-bis(trifluoromethyl)phenyl] carbamothioyl] isophtalamide for potentiometric sensor - Kook, Shih Ying; Lee, Yook Heng; Nurul Izzaty Hassan,; Siti Aishah Hasbullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A copper ion sensor based on a new bis-thiourea compound N1,N3-bis[[3,5-bis(trifluoromethyl)phenyl]carbamothioyl]isophthalamide (or TPC) as neutral carrier was investigated. The immobilization of the TPC into poly(n-butyl acrylate) (pBA) membrane via drop casting and the sensor was characterized by potentiometry. The sensor fabricated from TPC only showed a good Nernstian response towards copper ion with a sensitivity slope of 28.81±0.53mV/decade in the range of 1.0 × 10-6 - 1.0 × 10-4 M. The limit of detection of this sensor was found to be 6.11 × 10-7 M and with short sensor response time (60 - 80 s). This sensor also demonstrated reversibility and reproducibility with 3.69% and 1.84% (Relative Standard Deviation, RSD), respectively. Based on the separate solution method (SSM), the logarithm selectivity coefficients were better than -2.00 for monovalent, divalent and trivalent cations and this confirmed that the sensor exhibited good selectivity towards copper ion. The sensor could attain optimum function without the need in the inclusion of either lipophilic anions as a membrane additive nor plasticizer as a membrane softener. Thus, these are the main advantages. The addition of lipophilic anions into the pBA membrane could cause the sensitivity and selectivity of the copper ion sensor based on ionophore TPC to deteriorate.